Analisis Butir Soal Tema 3 “Peduli Terhadap Makhluk Hidup” Kelas IV SDN 2 Kertaraharja Tahun Pelajaran 2021/2022 - Refa Tiwi Alia Fatin; Sekarsari Nurdini; Siti Farkhanah; Bella Belinda (Universitas Bengkulu, 2022)
This study aims to determine the feasibility of the question items compiled by researchers for multiple choice tests on theme 3